2020
DOI: 10.1097/wnp.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Agreement Between Critical Care Providers for Background Classification and Seizure Detection After Implementation of Amplitude-Integrated Electroencephalography in Neonates, Infants, and Children

Abstract: Purposes: Amplitude-integrated EEG (aEEG) has been widely developed in neonatal intensive care unit, but few studies focused on pediatric intensive care unit. Furthermore, reliability of aEEG under real-life conditions is unknown. Methods: Participants were nurses from a 12-bed pediatric intensive care unit in a referral university hospital in France. Amplitude EEG was implemented after standardized training, including e-learning course, individual feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…It is easy for clinicians to learn how to perform aEEGs, even if they are not EEG experts. One study found that, after a short training period, PICU personnel performed well when it came to detecting severely altered background patterns using the Hellström–Westas classification (kappa 0.71, 95% confidence interval 0.57–0.85), but moderate changes were more difficult to identify 16 . Another study explored whether medical students improved how they interpreted trends in a modified aEEG when it came to identifying wakefulness, sleep and encephalopathic patterns compared to conventional EEG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is easy for clinicians to learn how to perform aEEGs, even if they are not EEG experts. One study found that, after a short training period, PICU personnel performed well when it came to detecting severely altered background patterns using the Hellström–Westas classification (kappa 0.71, 95% confidence interval 0.57–0.85), but moderate changes were more difficult to identify 16 . Another study explored whether medical students improved how they interpreted trends in a modified aEEG when it came to identifying wakefulness, sleep and encephalopathic patterns compared to conventional EEG.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to reports on seizures, research suggests that the background pattern may have diagnostic value. [14][15][16][17] We do not know how common the use of the aEEG actually is in older infants and children. A telephone survey carried out in East England found that only one of the 17 hospital general paediatric wards used aEEG and another had access to conventional EEG oncall/during weekends.…”
Section: Use Of Aeeg In Paediatric Intensive Care Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clancy et al (2011), showed a moderate, positive association between grades of EEG and aEEG background, although the distribution of grades was significantly different 24 . Inter‐rater agreement of seizure detection by experts using EEG was generally high ( κ = 0.827) but reduced when seizures were infrequent or of short duration 25,26 . There was significant differences between the visual review of aEEG and EEG for the detection of neonatal seizures; 27 differences that could be resolved using a joint interpretation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple educational interventions have shown that it is possible to enable non-experts to rapidly set up and interpret EEG at the bedside [11][12][13]. However, a comprehensive overview of these training programs, including the methods used, outcomes obtained, and potential pitfalls, remains lacking.…”
Section: Introductionmentioning
confidence: 99%